Enhancing Sustainable Concrete Properties by Green Vegetable Substance - Hasan Abdulabbas, Zainab; Asad Salih, Marwa; Talib Jasim, Ali (International Journal of Engineering and Technology, 2018)
From several points of view, disposal of waste materials in an environment is respected to be a significant problem because of its very low biodegradability and existence in huge quantities. Waste of plastic and metal bottles caps, cans of juices and soft drink, and tires rubber being among the most pronounced. This study was conducted to evaluate the efficiency of reusing these waste materials in concrete production and solve the segregation problem. As segregation increases in concrete involving these waste materials due to lighter weight of them relative to nature aggregate, therefore, attention was intensive on using natural product (Gum Arabic) that is an environmentally friendly chemical material for improving concrete properties. The conducted tests include; compressive strength, flexural strength, splitting tensile strength, density, water absorption, and ultrasonic pulse velocity. The results showed that replacing the volume of coarse aggregate by 25% compacted bottles caps and pull-tab of cans, 20% the plastic bottle caps, and 25% tires rubber shreds used decreased the mechanical properties of concrete to some extent less than reference mix and they were enhanced by employing Gum Arabic. In addition, the employment of Gum Arabic as liquid in concrete mixes developed the mechanical properties of concrete, reduced segregation, however raised the water absorption percent and declined the density of concrete.Â Â